Pilot optimization for OFDM in the RSSB system - Chen, Long; Yang, Ziteng; Yu, Qian (Frontiers in Physics, 2023)
In this paper, we propose and simulate a reversely single sideband (RSSB) system with orthogonal frequency division multiplexing (OFDM) signal transmission based on the improved pilot interval scheme and pilot power scheme. To avoid sub-carrier suffering from the signal-signal beat interference (SSBI), the improved pilot interval scheme uses more pilots in areas where channel conditions are relatively good. The improved pilot power scheme compensates for frequency selective fading by increasing the pilot power in areas where channel conditions are relatively poor. According to the simulation, the generated 60-GHz optical millimeter wave with 2.5G bandwidth OFDM signal is delivered over 100-km standard single-mode fiber (SSMF). The improved pilot interval scheme and the improved pilot power scheme can increase system receiving sensitivity by 2dB, respectively. These schemes can enhance the system performance without increasing the complexity of the algorithm and the costs of the RSSB system.